Fibroblast Growth Factor 21 (FGF21), Free Fatty Acid (FFA), High Sensitivity C-reactive Protein (hsCRP) and Homeostasis Model Assessment of Insulin Resistance (HOMA-IR) Among Indonesian Obese Non-Diabetic Males - Yani Lina; Gatot Susilo Lawrence; Andi Wijaya; Suryani As'ad (The Prodia Education and Research Institute (PERI), 2009)
BACKGROUND: Fibroblast growth factor-21 (FGF21) is known as an important endocrine and paracrine regulator of metabolic homeostasis. Recent studies have shown that FGF21 attenuates lipolysis in human adipocytes, which is suggested as a FGF21's mechanism as anti-hyperlipidemia, anti-hyperglycemia and anti-obesity. The aim of this study was to measure the correlation between FGF21, FFA, hsCRP and HOMA-IR among Indonesian obese non diabetic males.METHOD: The study was observational with cross sectional design. The analysis was done in 137 subjects aged 30-60 years with non diabetic abdominal obesity. We measured the biochemical markers FGF21, FFA, hsCRP, fasting insulin and fasting glucose. We also measured weight, height, waist circumrefence (WC), creatinine, serum glutamin oxaloacetic transaminase (SGOT), and serum glutamic pyruvic transaminase (SGPT), systolic blood pressure (SBP) and diastolic blood pressure (DBP). Correlation between markers was measured using Pearson and Spearman's analysis. RESULT: There were significant positive correlations between FGF21-HOMA-IR (r=0.314, p=0.000); FGF21-WC (r=0.173, p=0.043); FFA=hsCRP (r=0.270, p=0.001); and WC-HOMA-IR (r=0.279, p=0.001). There was significant negative correlation between FGF21-FFA (r=-0.038, p=0.657) and FGF21-hsCRP (r=-0.061, p=0.482). CONCLUSION: In this study we found that although there was no significant correlation, FGF21 might act as an anti-lipolytic and anti-inflammation agent among Indonesian obese non-diabetic males. Our findings agree with results of previous studies that the positive correlation between FGF21-WC and FGF21-HOMA-IR moght occur as a compensatory mechanism or resistance to FGF21 in obesity.KEYWORDS: Obesity, FGF21, FFA, hsCRP, HOMA-IR